Alternative plasticizer, 4‐cyclohexene‐1, 2‐dicarboxylic acid dinonyl ester, for blood containers with protective effects on red blood cells and improved cold resistance. Issue 3 (13th May 2017) - Morishita, Yuki; Nomura, Yusuke; Fukui, Chie; Fujisawa, Ayano; Watanabe, Kayo; Fujimaki, Hideo; Kumada, Hidefumi; Inoue, Kaoru; Morikawa, Tomomi; Takahashi, Miwa; Kawakami, Tsuyoshi; Sakoda, Hideyuki; et al.
Abstract: Di (2‐ethylhexyl) phthalate (DEHP), a typical plasticizer used for polyvinyl chloride (PVC), is eluted from PVC‐made blood containers and protects against red blood cell (RBC) hemolysis. However, concerns have arisen regarding the reproductive and developmental risks of DEHP in humans, and the use of alternative plasticizers for medical devices has been recommended worldwide. In this study, we propose that the use of a novel plasticizer, 4‐cyclohexene‐1, 2‐dicarboxylic acid dinonyl ester (DL9TH), could help produce more useful and safe blood containers. PVC sheet containing DL9TH and di (2‐ethylhexyl) 4‐cyclohexene‐1, 2‐dicarboxylate (DOTH) provides comparable or superior protective effects to RBCs relative to PVC sheet containing DEHP or di‐isononyl‐cyclohexane‐1, 2‐dicarboxylate (DINCH ®, an alternative plasticizer that has been used in PVC sheets for blood containers). The total amount of plasticizer eluted from DOTH/DL9TH‐PVC sheets is nearly the same as that eluted from DEHP‐PVC sheets. In addition, DOTH/DL9TH‐PVC has better cold resistance than DEHP‐ and DINCH ® ‐PVC sheets. In vitro and in vivo tests for biological safety based on International Organization for Standardization guidelines (10993 series) suggest that the DOTH/DL9TH‐PVC sheet can be used safely. Subchronic toxicity testing of DL9TH in male rats in accordance with the principles of Organisation for Economic Co‐operation and Development Test Guideline 408 showed that DL9TH did not induce adverse effects up to the highest dose level tested (717 mg/kg body weight/day). There were no effects on testicular histopathology and sperm counts, and no indications of endocrine effects: testosterone, thyroid‐stimulating hormone, follicle‐stimulating hormone, and 17β‐estradiol were unchanged by the treatment, compared with the control group. © 2017 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 106B: 1052–1063, 2018.